GLOBAL PERSPECTIVES ON THE CRIMINALIZATION OF CUSTODIAL TORTURE IN INTERNATIONAL HUMAN RIGHTS LAW - Muhammad Shan (`, 2025)
Custodial torture remains a pervasive violation of human rights globally, despite its unequivocal prohibition under international law and Islamic jurisprudence. This article examines the criminalization of custodial torture through the lens of international human rights frameworks, with a focus on Pakistan’s legislative efforts, such as the Torture, Custodial Death, and Custodial Rape (Prevention and Punishment) Act, 2022. While international instruments like the United Nations Convention Against Torture (CAT) and the Universal Declaration of Human Rights (UDHR) establish absolute prohibitions against torture, implementation gaps persist, particularly in states where institutional impunity and political resistance undermine accountability. The article highlights the intersection of Islamic principles which condemn torture as a violation of human dignity with global human rights norms, arguing for their harmonization to strengthen legal frameworks. Case studies from Pakistan reveal systemic challenges, including underreporting, marginalization of vulnerable groups, and weak enforcement mechanisms. The role of international bodies, such as the UN Human Rights Council, and civil society in combating impunity is also explored. Recommendations include legal reforms, judicial training, international sanctions, and technological oversight to deter abuses. The study underscores the need for a multifaceted approach, blending domestic legislative action with international cooperation, to eradicate custodial torture and uphold justice. Keywords: Custodial Torture, International Human Rights Law, Pakistan, Convention Against Torture (CAT), Islamic Jurisprudence, Impunity, Accountability, Legal Reforms